2011
DOI: 10.3233/jad-2011-101881
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Biomarkers in the Brain of a Mouse Model for Alzheimer's Disease: Mining of Microarray Data by Logic Classification and Feature Selection

Abstract: The identification of early and stage-specific biomarkers for Alzheimer's disease (AD) is critical, as the development of disease-modification therapies may depend on the discovery and validation of such markers. The identification of early reliable biomarkers depends on the development of new diagnostic algorithms to computationally exploit the information in large biological datasets. To identify potential biomarkers from mRNA expression profile data, we used the Logic Mining method for the unbiased analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 55 publications
4
82
0
Order By: Relevance
“…In a research conducted in 2001, researchers identified Alzheimer's biomarkers in a few mice [17], and again we had common results to an extent. However, it was necessary to find more accurate and more reliable results, so that this study would be conducted on human samples and with sampling of different brain segments.…”
supporting
confidence: 53%
“…In a research conducted in 2001, researchers identified Alzheimer's biomarkers in a few mice [17], and again we had common results to an extent. However, it was necessary to find more accurate and more reliable results, so that this study would be conducted on human samples and with sampling of different brain segments.…”
supporting
confidence: 53%
“…In a research conducted in 2001 in Saint Mateu, California, on Alzheimer disease, 31 genes had an over expression and 87 genes had a down expression which was completely consistent with the current study samples and some of the unknown genes were also added to the list of genes that previously had a role in the incidence of Alzheimer disease (21).…”
Section: Discussionmentioning
confidence: 99%
“…A long array of methods are used to perform such task, ranging from the more established parametric statistical analysis to non parametric techniques, to classification methods that have been developed in knowledge engineering and artificial intelligence. In this paper, we consider a method for extracting logic formulas from data that relies on a large body of literature in integer and logic optimization, originally presented in [1], that has been largely and successfully applied to different problems in bioinformatics ( [2], [3], [4], [5], [6]). Such method is based on the iterative solution of Minimum Cost SAT Problems and is able to extract logic formulas in DNF form that possess interesting features for their interpretation.…”
mentioning
confidence: 99%